Pentecostal theology' as contradictio in terminis a perspective on the past and present - Nel, Marius (2017)
The Pentecostal movement, especially in its early days, has been accused of anti-intellectualism and a lack of a developed theological tradition, and it is conceded that it is justifiably so. In the early movement, to speak of Pentecostal Theology' represented a contradiction in terminis. It is argued in the first part that Pente-costalism's anti-intellectualism should be understood (and justified) as a historical phenomenon, in terms of the contributions of several prominent Pentecostal leaders, Richard Spurling, William Parham, William Seymour and David Myland. The conclusion is that the movement's anti-intellectualism served as a reaction to what it perceived to be the dangers that theology' posed, as represented by creedalism and formalism. Against this, Pentecostals emphasised Spirit baptism and the resultant life guided by the Spirit as prerequisites for the development of the believer's spiritual dimension, that might at times stand in contrast to intellectual capabilities and endavours. Its restorationist motive required the Pentecostal movement to return to the experience and power of the earliest Church, driven by its apocalyptic-eschatological expectation of the imminent second coming of Christ. In the second part, the contemporary Pentecostal movement's stance on theology' as well as its theological principles and contributions are described. Although Pentecostals originally made negative remarks about theology', today they define it in a specific manner that allow them to take seriously their own brand of theological enterprise. They base their theology on encounters with God through his Spirit, described in terms provided by biblical narratives and leading to a spirituality that occupies the affections as well as the minds of its practitioners. Although their theology has traditional elements that they share with other traditions, Pentecostals' spirituality requires that their theology should be based on first-hand experiences with God, resulting in some doctrines being defined in a manner that differs from other theological traditions. It is concluded that contemporary Pentecostal Theology' does not represent a contradictio in terminis any more.
Keywords: Anti-intellectualism; Experiential angle; Hermeneutics; Pentecostal Theology; Relational knowledge